Strategi Efektif Pencegahan Bullying di Sekolah Dasar melalui Pendekatan Pendidikan Karakter - Chairan Zibar L. Parisu (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Bullying in Elementary Schools is a serious problem that can have a negative impact on students' psychological and academic development. Character education is one of the effective approaches in preventing bullying behavior by forming positive values ​​in students. This literature study aims to examine various strategies for preventing bullying in Elementary Schools through a character education approach. Analysis was conducted on studies that discussed the integration of character values ​​in the curriculum, the role of teachers and parents, and the implementation of a supportive school environment. The results of the study indicate that effective prevention strategies include strengthening the values ​​of empathy, cooperation, and tolerance in students' daily lives. In addition, the involvement of all elements of the school in building an anti-bullying culture is essential. It is hoped that the results of this study can provide recommendations for educators in creating a safer and more inclusive school environment for all students.